2011
DOI: 10.1123/jpah.8.s2.s228
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of a Physical Activity Intervention Among Pregnant Women: The Behaviors Affecting Baby and You (B.A.B.Y.) Study

Abstract: Background Physical activity during pregnancy is associated with reduced risk of adverse maternal and fetal outcomes. However, the majority of pregnant women are inactive and interventions designed to increase exercise during pregnancy are sparse. We evaluated the feasibility and preliminary efficacy of an exercise intervention among a diverse sample of pregnant women. Methods The B.A.B.Y. (Behaviors Affecting Baby and You) Study is conducted at a large tertiary care facility in Western Massachusetts. We ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 59 publications
1
36
0
1
Order By: Relevance
“…32 In that study, Chasan-Taber et al found that women in the exercise intervention had lower declines in total physical activity compared with the health and wellness arm from before to after the intervention (-1.0 MET hours/day vs -10.0 MET hours/day, respectively; P = .03). The exercise arm also reported increases in physical activity during sports or exercise compared with a slight decrease in the health and wellness arm (0.09 MET hours/day vs -0.01 MET hours/day, respectively; P = .02).…”
Section: Discussionmentioning
confidence: 99%
“…32 In that study, Chasan-Taber et al found that women in the exercise intervention had lower declines in total physical activity compared with the health and wellness arm from before to after the intervention (-1.0 MET hours/day vs -10.0 MET hours/day, respectively; P = .03). The exercise arm also reported increases in physical activity during sports or exercise compared with a slight decrease in the health and wellness arm (0.09 MET hours/day vs -0.01 MET hours/day, respectively; P = .02).…”
Section: Discussionmentioning
confidence: 99%
“…La evaluación de la validez y confiabilidad de la aplicación del GPAQ en la ENS 2009-2010 demostró que la sobrestimación del cuestionario comparado con la medición objetiva efectuada con acelerómetros presentó un sobre reporte promedio de 548 minutos por semana, esta sobrestimación estaba asociada con ser: sexo hombre, tener menos de 8 años de educación y mayor IMC (15). Por lo tanto, al aplicar el modelo de corrección utilizado en la ENS 2009-2010 (1,15) el valor de suficientemente activo se reduce a sólo un 20,3%.…”
Section: Tabla II Descripción Del Tiempo De Actividad Física Total Y unclassified
“…However these concerns have not been founded within 'normal' healthy pregnancies and the guidelines have since changed (Duncombe et al 2009, Melzer et al 2010. The American College of Obstetricians and Gynaecologists (ACOG) have revised their guidelines to state that pregnant women, who are free of any health and pregnancy complications, can partake in moderate exercise up to 30minutes per day on most, if not all, days of the week (Artal et al 2003, Chasan-Taber et al 2011. Women who were previously classed as sedentary who wish to start exercising are recommended to build up to the stated amount gradually by starting with 15 minutes three times a week (Melzer et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore perhaps not unexpected that the majority of pregnant women are classed as inactive and do not meet the ACOG exercise guidelines (Haakstad et al 2009, Chasan-Taber et al 2011, Jackson et al 2011, Gaston et al 2012. Despite this, it could be that pregnancy is an opportune time for women who are classed as sedentary to change their exercise behaviours (Artal et al 2003), this is a time when they will potentially be in contact with the health system the most in their lives to date and could be motivated to change for the benefit of their growing child (Wadsworth 2007, Jackson et al 2011, O'Brien et al 2014.…”
Section: Introductionmentioning
confidence: 99%